The Important of Base Isolation Inflastic Parameters for Buildings with Long Natural Period - Perpustakaan UGM, i-lib ([Yogyakarta] : Kantor Wakil Rektor Bidang Kemahasiswaan dan Alumni UGM, 2003)
The application of base isolation has been proposed to protect buildings from damage during major earthquakes by lengthening the natural period in the elastic state. This strategy can be simply seen from common response spectrum in which longer natural period will cause smaller earthquake forces. However, the effectiveness of base isolation shall not be relied on its elastic behaviour only, especially for buildings that already have longer natural periods. In this case the effectiveness of base isolation in protecting the buildings from damage shall be relied on the inelastic behaviours of base isolation. This report discusses the role of inelastic parameters of base isolation in protecting a building that was not previously designed to resist an earthquake. From analytical case study, it is found that the inelastic parameters of yield force, Fy, and bi-linear factor parameters, r, should be taken as small as practical possible to optimise the effectiveness of base isolation in protecting buildings from damage during major earthquakes.